2020
DOI: 10.1016/j.eclinm.2020.100567
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis C virus care cascade in the New York City jail system during the direct acting antiviral treatment era, 2014–2017

Abstract: Background High patient turnover presents challenges and opportunity to provide hepatitis C virus (HCV) care in US jails (remand facilities). This study describes the HCV care cascade in the New York City (NYC) jail system during the direct-acting antiviral (DAA) treatment era. Methods Patients admitted to the NYC jail system from January 2014 through December 2017 were included in this retrospective cohort analysis. We describe rates of screening, diagnosis, linkage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Prior studies showed that treatment interruption as a result of early release or transfer can negatively impact the SVR rates among the incarcerated cohort [ 14 ]. While high SVR beyond 90% is widely reported among incarcerated-HCV patients remained in follow-up, SVR by intention to treat was significantly lower, ranging between 37–72% [ 18 , 20 , 22 - 24 ]. The difference is even more apparent among a larger cohort with high proportion of subjects being lost to follow-up [ 18 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies showed that treatment interruption as a result of early release or transfer can negatively impact the SVR rates among the incarcerated cohort [ 14 ]. While high SVR beyond 90% is widely reported among incarcerated-HCV patients remained in follow-up, SVR by intention to treat was significantly lower, ranging between 37–72% [ 18 , 20 , 22 - 24 ]. The difference is even more apparent among a larger cohort with high proportion of subjects being lost to follow-up [ 18 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While high SVR beyond 90% is widely reported among incarcerated-HCV patients remained in follow-up, SVR by intention to treat was significantly lower, ranging between 37–72% [ 18 , 20 , 22 - 24 ]. The difference is even more apparent among a larger cohort with high proportion of subjects being lost to follow-up [ 18 , 23 , 24 ]. In this study, we successfully maintained a high retention rate in this large incarcerated cohort by ensuring adequate treatment duration, thus avoiding unplanned treatment interruption leading to treatment default.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In more recent data from the DAA era, in the New York City jail system during 2014-2017, of 269 patients with HCV infection who started DAA treatment, 172 (64%) achieved documented SVR12, although there was a 16% subsequent reinfection rate, and the population-level SVR12 among all incarcerated HCV-infected patients was 3.2%. 19,20 International data on treatment of HCV infection among incarcerated persons are sparse, although 1 study assessed the HCV care cascade in prisons in Quebec, Canada, during 2017-2018 and found that 2 of 16 incarcerated HCV-infected patients achieved SVR12. 21 A more recent study from Taiwan with opt-in screening found that of 276 people in jail identified as having positive HCV serology (HCV exposure), 191 (69%) had HCV infection and 165 (60%) achieved SVR12 with DAA treatment.…”
mentioning
confidence: 99%